LEARNIS PLATFORM: KEY FEATURES, ADVANTAGES, DISADVANTAGES, AND CREATING A WEB QUEST - Karshiyeva, Dilnoza (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The article investigates the key features of Learnis platform, its advantages and disadvantages, and creating a web quest in this platform. In this article, information is provided on the issues of improving the methods of organizing new modern lessons, using innovative technologies, and developing the competence of designing lessons using Quest technologies. Method: formation of developments helps learners to develop their competencies such as creating project work based on innovative technologies, creating problem situations and discussing their solutions with a group. Results: Therefore, in this article, we revealed that designing lessons based on quest technology is an effective result. Novelty: In this article, information is provided on the issues of improving the methods of organizing new modern lessons, using innovative technologies, and developing the competence of designing lessons using Quest technologies